King Lear Based on the Play by William Shakespeare - Shakespeare, William (Sony Pictures, 2004)
Brook originally directed Scofield as Lear at the RSC in 1962 at Stratford. The radical, minimalist production, one of the first "bare stage" productions, followed the Quarto text. His relentlessly cold and unemotional film version was heavily influenced by the essay, "King Lear or Endgame", in which the Polish poet/critic/academic Jan Kott argued that Lear should be interpreted in terms of Samuel Beckett's New Theatre as a play devoid of any consolation, morality or universal justice. Brook's bleak film was set in a desolate, barren landscape. The violence is brutal - Brook depicts deaths which Shakespeare keeps off-stage - Cordelia's neck in the hangman's noose is heard to snap and Gonerill dashes out Regan's brains against a rock before killing herself. [www.rsc.org.uk]
Keywords: DVD-Video